Freedom of Religion and Belief in Higher Education: Between Policy and Practices - Zainurohmah Zainurohmah; Rizqiya Lailatul Izza; Indriana Firdaus; Fitria Damayanti; Baidhowi Baidhowi (Universitas Negeri Semarang, 2023)
Regulation is a set of rules formed to regulate the order of social life. Regulations also regulate various lines of life including religion. Religion is defined as man's belief in the existence of God including the ordinances of worship. Freedom of religion also needs to be applied in universities as evidence of Freedom of Religion and Belief. This study aims to find out how the regulation of religious freedom in Higher Education (Semarang State University Campus Study) from the point of view of Freedom Of religion And Belief. This study used normative juridical methods. In this study, it can be concluded that the procurement of houses of worship in universities is still very rare. This is because there are no regulations or policies that regulate this matter. However, there are also several universities that already have multi-religious houses of worship, one of which is Semarang State University. The construction of the house of worship aims to strengthen religious moderation through tolerance.